“It is the finest piece of government work that I know of anywhere”: The Influence of the Hydro-Electric Power Commission of Ontario on the Giant Power Survey of Pennsylvania, 1923-1927 - Sholdice, Mark (Scientia Canadensis, 2014)
Since its foundation in 1906, the Hydro-Electric Power Commission of Ontario exerted a major influence on the politics of electricity in the United States. American supporters of publicly-owned utilities saw the Hydro as a model worth emulating south of the border. Reformers who sought lower electric prices for consumers also looked to the Hydro for evidence of the technically-feasible lowest cost of producing and transmitting this source of energy. This paper will examine a specific instance when American Progressives sought to use the Hydro as both a source of information and inspiration for electric policy reforms: the Giant Power Survey of 1923-1927, an attempt by Pennsylvania Governor Gifford Pinchot to bring about lower electricity costs for consumers and to extend access to rural areas, through a mix of greater regulation and government action. The individuals involved in Giant Power came into close contact with Hydro officials for the vital administrative and technical information with which to argue for their cause; the Ontarians, however, had their own reasons to be wary of getting involved in a controversial proposal.